2021
DOI: 10.3390/ijerph182111026
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Psychological First Aid after Exposure to a Traumatic Event at Work among EMS Workers: A Qualitative Study

Abstract: Managing post-traumatic stress reactions in the first few days after exposure to a potentially traumatic event in the course of one’s work remains a challenge for first responder organizations such as Emergency Medical Services (EMS). Psychological First Aid (PFA) is an evidence-informed approach to reducing initial distress and promoting short- and long-term coping strategies among staff in the aftermath of exposure. PFA provided by peer helpers is considered a promising solution for first responder organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These recommendations are congruent with the Dynamic Sustainability Framework (DSF), which was developed for the implementation of health interventions in organizations ( Chambers et al, 2013 ), as well as the current literature on PFA’s implementation in organizations. Research effectively showed that PFA training gives responders the confidence to use the intervention with prospective beneficiaries even if they were not trained in mental health ( McCabe et al, 2011 ), and that the adherence of Emergency Medical Services workers as PFA-responders was based on their confidence and ability to provide an adapted intervention as well as their feeling of being adequately equipped ( Tessier et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These recommendations are congruent with the Dynamic Sustainability Framework (DSF), which was developed for the implementation of health interventions in organizations ( Chambers et al, 2013 ), as well as the current literature on PFA’s implementation in organizations. Research effectively showed that PFA training gives responders the confidence to use the intervention with prospective beneficiaries even if they were not trained in mental health ( McCabe et al, 2011 ), and that the adherence of Emergency Medical Services workers as PFA-responders was based on their confidence and ability to provide an adapted intervention as well as their feeling of being adequately equipped ( Tessier et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that the adaptation of PFA was based on authors’ experience with police officers seeking psychotherapy services at the Montreal Trauma Studies Center. Moreover, a similar project was conducted with paramedics (see Tessier et al, 2021 ). First, the context in which PFA could be used was broadened.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in many areas of occupational behavioral health practice-and in fire and EMS organizations particularly-debriefing and related interventions are still widely used. In response, efforts to provide alternatives to CISD, such as Psychological First Aid, have gained momentum [45].…”
Section: Introductionmentioning
confidence: 99%